2018
DOI: 10.18666/jorel-2018-v10-i2-8191
|View full text |Cite
|
Sign up to set email alerts
|

Curating a Public Self: Exploring Social Media Images of Women in the Outdoors

Abstract: She is the Chair of the Australian Tertiary Outdoor Education Network (ATOEN) and has been involved in wilderness studies and outdoor education for over 35 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 34 publications
(20 reference statements)
1
20
0
Order By: Relevance
“…In the context of sport, visuality is often studied and seen as an extension of the physical experience. Research shows that recreational sports practitioners use photo-sharing practices to engage in the collective reproduction of style (Woermann 2012), assert their place as part of the sports community (Olive 2015), and curate their athletic self-presentation (Gray et al 2018). Regarding community building among mountain bikers, McCormack (2018) argues that mediated rituals, such as photo sharing, extend and strengthen social relations between practitioners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of sport, visuality is often studied and seen as an extension of the physical experience. Research shows that recreational sports practitioners use photo-sharing practices to engage in the collective reproduction of style (Woermann 2012), assert their place as part of the sports community (Olive 2015), and curate their athletic self-presentation (Gray et al 2018). Regarding community building among mountain bikers, McCormack (2018) argues that mediated rituals, such as photo sharing, extend and strengthen social relations between practitioners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These absences continue to maintain social, political and economic inequality within outdoor and adventure spaces (Comrie & McMillan, 2013). Whilst many studies have indicated that lack of representation may limit particular individuals' participation in outdoor activities, recent research demonstrates that individuals are turning to social media to showcase and amplify their own outdoor experiences through self-presentation (Gray, Norton, Breault-Hood, Christie & Taylor 2018;Stanley, 2020;Weatherby & Vidon, 2018). In the last decade, social media sites (SMSs) have enabled people to produce and share knowledge, emotions and experiences far more widely than in the past (Kietzmann, Hermkens, McCarthy & Silvestre, 2011;Thorpe, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In light of media's potential to both reinforce and challenge hegemonic discourses, it is imperative to continue to examine the interplay between media affordances, representations and experiences of the outdoors. However, research investigating outdoor media and, in particular, women's user-generated outdoor social media content and the notion of self-presentation is still in its infancy (Frazer & Anderson, 2018;Gray et al, 2018;Kling, Margaryan & Fuchs, 2018;Lyu, 2015;Stanley, 2020;Weatherby & Vidon, 2018;Zink & Kane, 2015). Calls have been made for further exploration of user-generated content (UGC) on SMSs as well as actual participation behaviours and preferences, particularly through a gendered lens (Frazer & Anderson, 2018;Kling et al, 2018;Weatherby & Vidon, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Either way, a more explicit focus on identified groups would help to explore these options. Going beyond the above focus on hikers who have set off to explore places outside the city, what about runners-when and in what ways might their smartphones augment experiences with the natural environment(Bamberg et al, 2018)?Turning to other groups,Gray et al (2018), for example, have explored how gender serves to shape the depiction of outdoor experiences on Instagram, which takes us back to some of the important self-presentation issues with which we began. Here,Truong and Clayton (2020), for example, point to the value of speaking with 'content creators' about how they depict the natural world.…”
mentioning
confidence: 99%